Influence of the Type of Macrocycle on the Stabilisation of the High Oxidation State of the Manganese Ion and Electrode Processes - Danuta Tomczyk; Sławomira Skrzypek; Piotr Seliger (Molecules)
Dinuclear di-µ-oxo complexes of Mn3+ and Mn4+ ions, and mononuclear complexes of Mn3+ ions with tetraazamacrocycles ([12]aneN4, [14]aneN4, [15]aneN4) and C-substituted derivative (Me6[14]aneN4) as well as mononuclear complexes of Mn2+ ions with N-substituted derivatives ((N-Me)2[14]aneN4, (N-Me)4[14]aneN4, (N-Me)Me2py [14]aneN4) and with oxo2[14]aneN4 were studied. Based on spectroscopic (UV VIS and IR) and conductometric studies, the types of synthesised complexes (cis or trans isomers of mononuclear Mn3+ complexes, oxygen bridges and class II according to Robin and Day classification for dinuclear complexes) were determined. On the basis of voltammetric and spectroelectrochemical studies, trans-cis isomerisation at the level of Mn2+ ion complexes and cis-trans isomerisation at the level of Mn3+ ion complexes were demonstrated for complexes of ligands with free C positions. The N-substituted derivatives oxidise according to the EC mechanism, in which the follow-up reaction is a disproportionation reaction. The thermodynamic stabilisation of Mn3+ ions was determined by comparing the formal potentials (Ef0), the disproportionation constants (k1) and the formation constants (βIII). The study showed the possibility of oxidation of mononuclear, pseudo-octahedral Mn3+ ion complexes to dinuclear complexes and the greatest stabilisation of Mn3+ ions, both in monomers and dimers of ligands with free N positions.